ONLINE CALCULATOR IN DIAGNOSTICS OF FUNCTIONAL STATE AND BODY MASS INDEX - Shutova, T.N.; Andryushchenko, L.B.; Drayko, N.Yu.; Zvereva, S.N. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop a digital tool for the rapid implementation of functional diagnostics and further recommendations on physical culture. Methods and structure of the study. A mobile application in the form of an online calculator made it possible to digitize the following existing formulas: the coefficient of endurance of the cardiovascular system, the level of regulation of the cardiovascular system, the vital index, the Skibinski circulatory-respiratory coefficient, the body mass index, the vegetative Kerdo index, the index of functional changes circulatory systems. And also to assess the level of motor activity of students of the Plekhanov Russian University of Economics (279 people, February 2022). Results and conclusions. Diagnostics with the help of a digital tool revealed the optimal indicators of body mass index, physical activity of students below the physiological norm. At the same time, low values ​​of VC, the level of regulation of the cardiovascular system, the vital index and the index of the functional capabilities of the circulatory system in young men were determined. Almost none of the index revealed high, above average and average values, except for the coefficient of endurance of the cardiovascular system in young men. In this regard, the importance of regular physical activity, "informal participation" in sports, organization of competitions "For all" (General physical training, billiards, tug of war), master classes using digital technologies are noted. Thanks to the developed application, efficiency, interactivity, personality-oriented orientation of teaching in physical culture and sports at the university was achieved. Undoubtedly, this digital service aroused high interest among the target student audience, it meets the requirements of the digital educational ecosystem for Physical Culture and Sports at the university.